2012
DOI: 10.1029/2012gl052366
|View full text |Cite
|
Sign up to set email alerts
|

Equatorially confined warm trapped ions at around 100 eV near the plasmapause

Abstract: [1] Near the equatorial plasmapause at around 4-5 Earth radius (R E ) geocentric distance, pancake distributed tens of eV ions are sometimes found, as previously reported by Olsen et al. (1987). Cluster CIS data during perigee tra- + ratio is much less than 5% for the majority of the cases. Citation: Yamauchi, M.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…However, they only reported five of such events, all of them occurring at energies < 1 keV and within the first 13 months of CIS observations. While there have been numerous observations and studies of heavy ions in the magnetosphere, most of them have covered higher energies (typical energies of the ring current, >50 keV) [Keika et al, 2006;Gerrard et al, 2014aGerrard et al, , 2014bKronberg et al, 2015], or lower energies (sub-keV energies) [Yamauchi et al, 2012], or have considered only O + [Sharp et al, 1976;Kistler et al, 1999;Greenspan and Hamilton, 2002;Korth et al, 2002;Mitchell et al, 2003;Keika et al, 2006Keika et al, , 2013Ebihara et al, 2009;Maggiolo and Kistler, 2014;Kronberg et al, 2015], or only He + [Yamauchi et al, 2014], or have focused solely on storm times [Fu et al, 2001;Greenspan and Hamilton, 2002;Ebihara et al, 2009;Forster et al, 2013], or have covered larger geocentric distances (beyond geostationary distance) [Kistler et al, 1990[Kistler et al, , 2006Nosé et al, 2009;Mouikis et al, 2010;Maggiolo and Kistler, 2014]. Overall, there have been more studies on O + than on He + in the inner magnetosphere, probably because O + ions are normally more abundant and contribute more significantly to the plasma sheet and ring current mass density.…”
Section: Introductionmentioning
confidence: 99%
“…However, they only reported five of such events, all of them occurring at energies < 1 keV and within the first 13 months of CIS observations. While there have been numerous observations and studies of heavy ions in the magnetosphere, most of them have covered higher energies (typical energies of the ring current, >50 keV) [Keika et al, 2006;Gerrard et al, 2014aGerrard et al, , 2014bKronberg et al, 2015], or lower energies (sub-keV energies) [Yamauchi et al, 2012], or have considered only O + [Sharp et al, 1976;Kistler et al, 1999;Greenspan and Hamilton, 2002;Korth et al, 2002;Mitchell et al, 2003;Keika et al, 2006Keika et al, , 2013Ebihara et al, 2009;Maggiolo and Kistler, 2014;Kronberg et al, 2015], or only He + [Yamauchi et al, 2014], or have focused solely on storm times [Fu et al, 2001;Greenspan and Hamilton, 2002;Ebihara et al, 2009;Forster et al, 2013], or have covered larger geocentric distances (beyond geostationary distance) [Kistler et al, 1990[Kistler et al, , 2006Nosé et al, 2009;Mouikis et al, 2010;Maggiolo and Kistler, 2014]. Overall, there have been more studies on O + than on He + in the inner magnetosphere, probably because O + ions are normally more abundant and contribute more significantly to the plasma sheet and ring current mass density.…”
Section: Introductionmentioning
confidence: 99%
“…Yamauchi et al . [] reported that about one third of the equatorially trapped warm ions [e.g., Olsen et al ., ; Blanc et al ., ] include the He + signature at higher energies than H + . However, the equatorially trapped warm ions are found at all MLT and all geomagnetic conditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Although this He + event lasted nearly an hour, which is enough to cause some dispersion at this energy according to both past observations and simulations [ Yamauchi et al ., , ], the energization location is expected to be close to the spacecraft location because there is no energy‐time (energy‐latitude) dispersion in Figures b, h, and n. Instead, the highest He + energy flux density was found at a rather constant energy (around 70 eV) while the intensity decreased during 08:01–08:08 UT in Cluster‐1 and 08:23–08:32 UT in Cluster‐4.…”
Section: Cluster Observationsmentioning
confidence: 94%
“…Fig. 10 shows one such example observed by Cluster (Yamauchi et al, 2012). Just limiting to the geocentric distance that Cluster traversed (4.0-4.5 R E at equator) and to ions more than 30 eV (strong heating), these ions are found nearly half the noon-dusk traversals during solar maximum, while probability is slightly lower in the night-dawn traversals because these ions are normally found at shorter geocentric distance there.…”
Section: Dynamics Of Cold Plasmaspheric Ionsmentioning
confidence: 98%
“…Cluster hot ion energy-time spectrograms of differential energy fluxes (keV cm −2 s −1 str −1 keV −1 ) during perigee traversal on 3 January 2002(Yamauchi et al, 2012). The most field-aligned sector and the most perpendicular sectors to the geomagnetic field are plotted.…”
mentioning
confidence: 99%